Influence of shear stress fluctuation on bed particle mobility - Cheng, Nian-Sheng (2012)
Whether or not a sediment particle is entrained from a channel bed is associated with both average bed shear stress and shear stress fluctuation, the latter being flow-dependent and also related to bed irregularities. In the first part of this study, a preliminary analysis of possible fluctuations induced by bed roughness is presented for the case of an immobile plane bed comprised of unisized sediments. The result shows that the roughness-induced variation is generally comparable to that associated with near-bed turbulence, and both variations can be approximated as log-normal in terms of probability density distribution. The bed particle mobility is then analyzed by considering the effects of shear stress fluctuations. The relevant computations demonstrate that with increasing shear stress fluctuations, the probability of the mobility of a bed particle may be enhanced or weakened. For the case of low sediment entrainment, the probability is increased by turbulence. However, the probability may be reduced by the shear stress fluctuation if the average bed shear stress becomes relatively higher. This study shows that the critical condition for initial sediment motion could be overestimated if the Shields diagram is applied for the condition of flows with high turbulence intensities.